(untitled) (Islamic Sciences Journal, 2023)
The research is based on devising models of the legal purposes of Dr. Wahba Al-Zuhaili through his books on the principles of jurisprudence and interpretation. Due to the many types of purposes, their divisions, and their ranks, the researcher has limited the discussion in this research to the five necessary purposes, which are religion, soul, mind, offspring, and money. The research presents examples of the purposes of general legislation, such as the purpose of justice, moderation, moderation, non-arbitrariness, inclination, and injustice, to make it easier for the Muslim to know what God Almighty wants, whether by His commands and prohibitions, or by what is permissible or forbidden. Accordingly, the research introduces a contemporary scientist, and shedding light on his biography and scientific efforts. The research is divided into two sections: - section one deals with the meaning and types of purposes, and the definition of Dr. Al-Zuhaili - section two includes two requirements, the first contains examples of necessary objectives, and the second includes examples of general legislative objectives.